2009
DOI: 10.1007/s10499-009-9296-9
|View full text |Cite
|
Sign up to set email alerts
|

Lack of essential fatty acids in live feed during larval and post-larval rearing: effect on the performance of juvenile Solea senegalensis

Abstract: Despite the large progress obtained in recent years, Senegalese sole (Solea senegalensis) production of high quality juveniles is still a bottleneck. This paper examines the effect of larval and post-larval lipid nutrition on juvenile performance and quality. Four dietary treatments were tested: A-enriched Artemia spp. (EA); B-non-enriched Artemia spp. (NEA); C-EA during the pelagic larval period and NEA after larval settlement; D-50% EA and 50% NEA. Juvenile fatty acid profile at 60 days after hatching (DAH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 32 publications
3
11
0
Order By: Relevance
“…Among nutrients known to interfere with bone development, dietary lipids and, particularly, highly unsaturated fatty acids (HUFA) and essential fatty acids (EFA), play a crucial role at first feeding in fish larvae (Izquierdo et al., 2000; Tocher, 2003, 2010) . In previous studies on different fish species, attention has mainly been paid to investigate the effects of dietary docosahexaenoic acid (22:6n−3, DHA) and eicosapentaenoic acid (20:5n−3, EPA) on bone formation (Kjørsvik et al., 2009; Roo et al., 2009; Dâmaso‐Rodrigues et al., 2010; Boglino et al., 2012). Although arachidonic acid (20:4n−6, ARA) is present in fish tissues in lower amounts than DHA and EPA, absolute amounts of dietary ARA may not be neglected, as well as its content relative to EPA and DHA (Moren et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Among nutrients known to interfere with bone development, dietary lipids and, particularly, highly unsaturated fatty acids (HUFA) and essential fatty acids (EFA), play a crucial role at first feeding in fish larvae (Izquierdo et al., 2000; Tocher, 2003, 2010) . In previous studies on different fish species, attention has mainly been paid to investigate the effects of dietary docosahexaenoic acid (22:6n−3, DHA) and eicosapentaenoic acid (20:5n−3, EPA) on bone formation (Kjørsvik et al., 2009; Roo et al., 2009; Dâmaso‐Rodrigues et al., 2010; Boglino et al., 2012). Although arachidonic acid (20:4n−6, ARA) is present in fish tissues in lower amounts than DHA and EPA, absolute amounts of dietary ARA may not be neglected, as well as its content relative to EPA and DHA (Moren et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the lack of HUFA and particularly DHA affects growth and development at first stages, playing a crucial role in the formation and functioning of the brain and retina. Recent studies have shown deleterious effects on Senegalese sole juveniles when reared on non‐enriched Artemia during the whole larval and postlarval stages (Dámaso‐Rodrigues et al., ). Furthermore, Navarro‐Guillén et al.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary lipids are a major source of energy and provide EFA and phospholipids, widely acknowledged as critical factors for success in larval fish rearing (Izquierdo et al., ), with a number of essential roles in metabolism and especially in bone metabolism, as demonstrated in mammals (Watkins et al., ). Several studies have highlighted the negative effects of diets deficient in EFA and phospholipids on flatfish larval growth performance, metamorphosis and survival (Tzoumas, ; Dickey‐Collas and Geffen, ; Izquierdo et al., ; Morais et al., ; Villalta et al., ) and the incidence of skeletal deformities (Dâmaso‐Rodrigues et al., ). It is well recognized that EFA, such as eicosapentanoic (20:5n–3, EPA), docosahexanoic (22:6n–3, DHA) and arachidonic (20:4n–6, ARA) acids, constitute some of the main nutritional factors that influence the growth and survival of marine fish larvae (Izquierdo and Koven, ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, most studies dealing with the effect of dietary EFA levels on skeletogenesis in fish have focused their investigation on the role of DHA and EPA (Villeneuve et al., ; Kjørsvik et al., ; Roo et al., ; Dâmaso‐Rodrigues et al., ; Boglino et al., 2012a; Izquierdo et al., ), but only a few have focused on investigating the effects of ARA on bone during fish larval development (Boglino et al., 2012b, ). ARA is the major precursor for eicosanoids synthesis, enhancing the immune system and resistance to stress, among other important physiological processes (Bell and Sargent, ), and it directly competes with EPA for the enzymes involved in prostaglandin biosynthesis.…”
Section: Introductionmentioning
confidence: 99%